Competitividade de destinos turísticos: fatores de demanda e desempenho - Oliveira, Carlyle Tadeu Falcão de (2013)
This thesis argues that the models for measuring the competitiveness of tourist destinations are structured essentially based on factors of supply and are designed primarily by experts and tourism professionals. So, the objective was to translate the tourist´s experience, in terms of competitiveness of the destination. This means to incorporate on the researches theme, the factor demand. In order to achieve this purpose, it was discussed: the major theories that explain the phenomenon of competitiveness and the models used to measure the competitive phenomenon. In this work, the main approaches, the influencing key elements of the competitiveness and the theoretical gaps of models were identified. It was discussed a method to capture the tourist’s experience at destinations which has been tested with different types of tourists by a qualitative research . The data were subjected to content analysis and in light of the Brazilian competitiveness model. The results showed that the competitiveness of destinations is evaluated mainly by supply factors and the assessment made by the tourism demand is only partially perceived. Therefore, if the demand factor could be incorporated to competitiveness studies it would afford destination managers to get more accuracy in their action.